Polydatin-Induced Shift of Redox Balance and Its Anti-Cancer Impact on Human Osteosarcoma Cells - Alessio Cimmino; Magda Gioia; Maria Elisabetta Clementi; Isabella Faraoni; Stefano Marini; Chiara Ciaccio (Current Issues in Molecular Biology)
Cancer cells demonstrate remarkable resilience by adapting to oxidative stress and undergoing metabolic reprogramming, making oxidative stress a critical target for cancer therapy. This study explores, for the first time, the redox-dependent anticancer effects of Polydatin (PD), a glucoside derivative of resveratrol, on the human Osteosarcoma (OS) cells SAOS-2 and U2OS. Using cell-based biochemical assays, we found that cytotoxic doses of PD (100–200 µM) promote ROS production, deplete glutathione (GSH), and elevate levels of both total iron and intracellular malondialdehyde (MDA), which are key markers of ferroptosis. Notably, the ROS scavenger N-acetylcysteine (NAC) and the ferroptosis inhibitor ferrostatin-1 (Fer-1) partially reverse PD’s cytotoxic effects. Interestingly, PD’s ability to hinder cell adhesion and migration appears independent of its pro-oxidant effect. Analysis of the oxidative stress regulators SIRT1 and Nrf2 at the gene and protein levels using real-time PCR and Western blot indicates an early oxidative response to PD treatment. PD remains effective under tumor-like conditions of hypoxia and serum starvation, and sensitizes OS cells to ROS-inducing chemotherapeutics like doxorubicin (DOX) and cisplatin (CIS). Importantly, PD exhibits minimal toxicity to non-tumorigenic cells (hFOB), suggesting a favorable therapeutic profile. Overall, our findings underscore that PD-induced redox imbalance plays a crucial role in its anti-OS effects, warranting further exploration into the molecular mechanisms behind its pro-oxidant activity.